The Influence of Price, Digital Marketing, and Consumer Reviews on Purchase Decisions in the Shopee Marketplace - Achmad Tarmizi; Dian Meliantari (Sean Institute, 2026)
This study aims to analyze the influence of price, digital marketing, and consumer reviews on purchase decisions in the Shopee marketplace among students of Dian Nusantara University, Jakarta. The research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 95 respondents who actively use the Shopee platform for online shopping. The data analysis technique employed in this study is multiple linear regression using SPSS software. The results indicate that price does not have a significant effect on purchase decisions, suggesting that consumers do not rely solely on price considerations when shopping in online marketplaces. Conversely, digital marketing has a significant positive influence on purchase decisions, indicating that promotional activities through digital channels play an important role in attracting consumer interest. Furthermore, consumer reviews were found to have the strongest influence on purchase decisions, highlighting the importance of electronic word-of-mouth in shaping consumer trust and reducing perceived risk in online transactions. These findings emphasize the importance of integrating digital marketing strategies with effective consumer review management to enhance purchase decisions in e-commerce platforms.